Menakar Jaminan Implementasi Al-Daruriyyat Al-Khams bagi Penghayat Kepercayaan dalam Keputusan Mahkamah Konstitusi - Imroatul Azizah (Proceedings of Annual Conference for Muslim Scholars, 2018)
The decision of the Constitutional Court to grant the judicial review petition for Law Number 23/2006 concerning Population Administration became viral because the Indonesian Ulama Council (MUI) opposed it. MUI is grounded in religion is one of the identity of citizens (Indonesia), and the indigenous beliefs is not a religion. Yet if looking at the definition of religion, indigenous beliefs including the religion of the earth (wad'i). Categorization of the celestial (samawi) religions and wad 'i existed at the time of the Prophet, the evidence when the Medina Charter was made, there were at least four groups of peoples: Paganism, Judaism, Christianity and Islam. Among the most important contents of Medina Charter is on Freedom of Religion (Paganism as a religion of wad'i also given freedom). Islam upholds the freedom of religion, the implementation of al-Daruriyyat al-Khams--li hifz al-din--finds its momentum, and the decision of the Constitutional Court which implies the assurance of the status of the believer of trust seen from the perspective of fiqh maqasidi is true.